Kunstwerk Computerspiel – Digitale Spiele als künstlerisches Material: Eine bildwissenschaftliche und medientheoretische Analyse - Schwingeler, Stephan (transcript, 2014)
»Computer Games as Works of Art« is the first well-founded aesthetic investigation of the computer game - a standard reference on the connection of art and computer games.